FAKTOR-FAKTOR YANG MEMENGARUHI DIVIDEND POLICY PERUSAHAAN MANUFAKTUR TAHUN 2018-2020 - Vern Rosalin; Thio Lie Sha (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to obtain empirical evidence of the effect of capital structure, growth in net assets, collateralizable assets and profitability on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling technique was purposive sampling where the number of samples selected was 21 companies. Data processing with multiple regression analysis using Eviews 12 software and Microsoft Excel 2019. The results show that profitability has a negative and significant effect on dividend policy, while capital structure, growth in net assets and collateralizable assets have no significant effect on dividend policy. The implication of this research is that the company's performance needs to be improved in order to maximize profits so that the prosperity of shareholders can be guaranteed through dividends distributed by the company.